Discrete-element method simulation of a model test of an embankment reinforced with horizontal–vertical inclusions. Issue 4 (1st August 2013) - Zhang, M.X.; Lu, Y.; Javadi, A.A.; Qiu, C.C.; Zhang, S.L.
Abstract : ABSTRACT: A series of laboratory model tests were conducted on unreinforced embankments, embankments reinforced with two-layer horizontal inclusions, and embankments reinforced with two-layer horizontal–vertical (H–V) inclusions. It is found that H–V inclusions perform better than horizontal inclusions in improving the bearing capacity and restricting the lateral displacements. In the light of the model test results, numerical simulations were performed, using the discrete-element method (DEM), to study the behavior of soil embankments reinforced with H–V inclusions. The effects of vertical inclusions on the distribution of contact forces and soil deformations were investigated. It is shown that when an embankment is reinforced with H–V inclusions, multiple vertical force-bearing columns develop inside it that redistribute the stresses and improve the bearing capacity. With the application of two-layer H–V inclusions, the failure surface is separated and the arcs become discontinuous. The horizontal reinforcing elements experience mainly tensile forces, and the vertical reinforcing elements provide resistance to soil particles. Compared with conventional horizontal inclusions, H–V inclusions restrict the movements of soil particles more effectively; consequently, the displacements of soil particles in both the horizontal and vertical directions are smaller. Overall, the DEM model can simulate the model tests accurately, and is helpful for analysis of the microscopic behavior of reinforced soil.